1984
DOI: 10.1002/j.1939-4640.1984.tb00770.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Glycerol and a Zwitter Ion Buffer System as Cryoprotective Media for Human Spermatozoa

Abstract: This study compared the cryoprotective effect of glycerol with that of a zwitter ion buffer system (TESTCY). Spermatozoa that are cryopreserved in the presence of glycerol possess a somewhat higher progressive motility immediately after thawing than those preserved in the presence of TESTCY. However, after a 1-hour incubation in glycerol-free medium, the progressive motilities of the glycerol- and TESTCY-treated spermatozoa become essentially identical. After 2 hours in culture medium, TESTCY-treated spermatoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Previous studies have suggested that an interaction may exist between rate of semen freezing and level of glycerol supplementation on cryosurvival of human sperm (Jeyendran et al -1984;. From Figures 1-4 it can be observed that sperm cryosurvival following CR compared with NCR freezing was not dependent on level of glycerol supplementation.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Previous studies have suggested that an interaction may exist between rate of semen freezing and level of glycerol supplementation on cryosurvival of human sperm (Jeyendran et al -1984;. From Figures 1-4 it can be observed that sperm cryosurvival following CR compared with NCR freezing was not dependent on level of glycerol supplementation.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies having suggested that the optimal concentration of glycerol for freezing human semen may be dependent on the rate of semen freezing (Jeyendran et al -1984;. The final objective of this study was to examine if the optimal concentration of glycerol for freezing human semen differed for the CR and NCR methods.…”
Section: Introductionmentioning
confidence: 99%
“…Two different cryopreservation media, TESTCY (Jeyendran et al 1984) and glycerol, were found to be suitable in about 33% of all our attempts at freezing semen, and in Over half of our most recent attempts. Semen was made 50% with TESTCY, or 10% with glycerol, over a 10-15 rnin period at room temperature, with gentle mixing.…”
Section: Methodsmentioning
confidence: 89%
“…The basic freezing media consisted of a zwitter ion buffer system (TEST) (8). To summarize briefly, the samples were prepared by titrating a 325-mOsm aqueous solution of N-Tris (hydroxymethyl) methyl 2-amino ethane sulfonic acid (CalBiochem, San Diego, CA) with a 325-mOsm aqueous solution of Tris (hydroxymethyl) amino methane (CalBiochem, San Diego, CA) to pH 7.5.…”
Section: Basic Freezing Mediummentioning
confidence: 99%